Transient hypoxemia after endotracheal tube extubation in a patient who received reversal of muscle relaxation using sugammadex after general anesthesia: A case report - Kang, Dong Hee; Seo, Han; Kim, Ju Deok (Indian Journal of Case Reports, 2024)
Post-operative respiratory depression is common in patients recovering from anesthesia and can result in fatal cardiopulmonary collapse, anoxic brain injury, and mortality. We report a case of a 54-year-old morbidly obese female patient who developed transient hypoxemia after general anesthesia. The patient with obstructive sleep apnea (OSA) underwent breast excision surgery. At the end of the surgery, her muscle function was fully restored using sugammadex. However, the patient developed transient hypoxemia in the post-anesthesia care unit. The clinician should keep in mind that OSA patients are likely to develop hypoxemia due to the residual sedative effects and airway obstruction despite the recovery of muscle function after anesthesia.